Airline labour law : a study of certain labour law rules in international air transport - Huang, Chu Cheng (McGill University, 1997)
This thesis examines problems related to particular labor laws currently applied in international air transport. This analysis is framed within the context of scholarly theory and judicial practice arising from various regimes of labor law governing industrial injury, the individual contract of employment, labor-management relations, and fair treatment in the civil aviation industry. A critical survey of labor regulations operating in the international air transport industry is provided through commentary on the principles formulated by judicial decisions and the theories which underlie their reasoning, helping to clarify both substantive and procedural labor laws affecting international air transport. A critical analysis of different categories of statutory labor law governing international air transport is also provided to assess the validity of commonly-erected conflict of labor law rules, thereby revealing the inadequacy of the single rule principle in view of the unique and perplexing regulatory interests which are inherent in aviation activity. The divergence between domestic labor statutes and Treaties of Friendship, Commerce and Navigation or bilateral air transport agreements also adds a more subtle aspect to the problems explored.
Identifier: https://escholarship.mcgill.ca/concern/theses/q237ht52f
Keywords: Air transport; Airline; Droit du travail; Labour law; Labour relations; Transportation

The resolution of labour conflicts : an international comparison - Rogowski, Ralf (European University Institute, 1992)
Keywords: Labour conflict (resolution); Labour law